2021
DOI: 10.1097/ju.0000000000001577
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation Improves Erectile Function in Patients with End-Stage Renal Disease: A Systematic Review and Meta-Analysis

Abstract: Erectile dysfunction has a lower prevalence in renal transplant recipients compared to dialysis patients. Despite this observation, the effect of renal transplantation on erectile function remains unknown. We aimed to assess the role of renal transplantation on erectile function and to determine potential factors improving or deteriorating erectile dysfunction. Materials and Methods: We conducted a systematic review and random effects meta-analysis of observational studies comparing erectile function preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…SRs analyzing evidence from only RCTs ( n = 20) [ 12 , 14 , 15 , 18 , 20 , 22 , 24 , 26 , 30 , 32 37 , 40 , 41 , 43 , 45 , 46 ], only NRSs ( n = 15) [ 19 , 21 , 23 , 31 , 39 , 42 , 44 , 47 54 ], or RCTs and NRSs ( n = 14) [ 7 11 , 13 , 16 , 17 , 25 , 27 29 , 38 , 55 ] were included into this methodological study. The main features of these 49 eligible SRs are summarized in Supplementary Table S 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SRs analyzing evidence from only RCTs ( n = 20) [ 12 , 14 , 15 , 18 , 20 , 22 , 24 , 26 , 30 , 32 37 , 40 , 41 , 43 , 45 , 46 ], only NRSs ( n = 15) [ 19 , 21 , 23 , 31 , 39 , 42 , 44 , 47 54 ], or RCTs and NRSs ( n = 14) [ 7 11 , 13 , 16 , 17 , 25 , 27 29 , 38 , 55 ] were included into this methodological study. The main features of these 49 eligible SRs are summarized in Supplementary Table S 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one upgrades of the certainty of evidence were due to a large effect (14.3%), dose–response (47.6%), and plausible confounding (38.1%). The authors of those SRs considered that the all plausible residual confounding in the included studies would reduce the demonstrated effect [ 21 , 29 , 53 ]. Downgrading for RoB was more common in SRs of RCTs (53.8%) than SRs of NRSs (49.3%), whereas downgrading for publication bias was more common in SRs of NRSs (1.2%) than SRs of RCTs (0.1%).…”
Section: Resultsmentioning
confidence: 99%
“…The hormonal changes indicated that the renal transplantation may potentially reverse the dysfunction in the pituitary‐Leydig cell axis in advanced uraemia. Former meta‐analyses conducted by other groups also found that kidney transplantation could restore the hormonal changes induced by dialysis (Kang et al., 2020; Pyrgidis et al., 2021).…”
Section: Discussionmentioning
confidence: 96%
“…With the popularity and maturity of transplantation technology, more and more patients with ESRD could choose renal transplantation for the substitution of dialysis. In the USA, nearly 22,000 ESRD patients live with a functioning kidney transplant (Pyrgidis et al., 2021). And approximately 100,000 Americans are still waiting for renal transplantation (Lundy & Vij, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation